Datierung des Tiefschnitts r/5 aus Areal R/III: (cEzbet-Rushdi/Tell el-Dabca) : Analyse der keramischen Funde - Michel, Vera (Ägypten und Levante, 2016)
The long term excavations carried out in Avaris, the ancient city of the Hyksos, presented a large variety of urban formations. Among them is the newly uncovered quarter in the area of Rushdi III (R/III). This paper will focus on the examination of the ceramic material from a test trench, which exposed the whole stratification in the southwestern sector of R/III, in order to get a better idea of the time frame of the settlement in this area. A comparison of the study results with the established pottery typology in Tell el-Dabca illustrates distinctive 15th Dynasty characteristics and indicates the domestic nature of the vessel compound. In conclusion this study suggests that the quarter R/III was settled during the complete 15th Dynasty and reused in the New Kingdom and the Late Period. However, the documentation and the evaluation, both of the material culture and of the architectural features in the area R/III are still in progress and further results are expected to come.